Collaboration of Vocational Training Institutions to Improve Vocational Students' Career Development Planning - Nakhma'ussolikhah; Meliyana; Hidayati; Budiman, Mohammad Arief (Cenderawasih Journal of Counseling and Education, 2023)
Facing the demand for a workforce that is trained and ready to work is a tough challenge for education in Indonesia. Vocational schools are needed that can be used as examples so that the education system that has been built currently can play its maximum role power expert professional to create school graduates who have career maturity. The aim is to motivate graduates so that they are confident in their abilities and ready to have a career in the world of work armed with the skills they acquired during their vocational education. Methodology study This with approach descriptive qualitative, pheno menological design or symptoms in detail as well as a response to the research subject. Technique Data collection includes observation , interview , documentation . The results of this research explain that career development stages are a way to position where individuals are in professional life . Career development stages are important for individuals to find the purpose of their life in the future. The stages of career development are as follows: First, initial career, the first stage where an individual enters an institution. The individual tries to get an idea of the skills and interests he has. Second, mid-career, the stage where individuals will experience a transition of change in their career, due to the acquisition of information and career guidance training that has been obtained. The third final career, the stage at which an individual can be productive with a career commitment that has become his goal, also has long-term planning. Then there are two strategies for implementing career development programs for students, namely a comprehensive strategy and an approach strategy for students. Keywords : Collaboration , Plan Career , Development Potency